Superior high-temperature oxidation resistance of nanocrystalline 304 austenitic stainless steel containing a small amount of Si. (November 2021) - Cai, X.C.; Ding, S.J.; Jin, S.B.; Xu, L.D.; Liu, G.Y.; Sun, B.R.; Shen, T.D.
Abstract: Improving the high-temperature oxidation resistance of steels by excessive Si addition to form a continuous silica healing layer would deteriorate the mechanical, welding and irradiation properties. Here, we report a thermally stable nanocrystalline 304 (NC-304) austenitic stainless steel with a low Si content (less than 1 wt.%) and superior high-temperature oxidation resistance. The segregated Si at the grain boundaries (GBs) of NC-304 presets a nanoscale Si-enriched network for the formation of a continuous SiO2 GB network during the high-temperature oxidation. Besides, the high-density La-Si-O-rich nanoprecipitates can serve as heterogeneous formation sites for SiO2, promoting the formation of a continuous SiO2 phase along the GB network. The unique nanocrystalline microstructure and element distribution feature of Si in NC-304 accelerate the construction of a continuous SiO2 healing layer, which effectively eliminates the breakaway oxidation found in coarse-grained 304 counterpart and significantly reduces the high-temperature oxidation rate at least to 1000 °C. Graphical abstract: Image, graphical abstract